Indoor air quality level influence sick building syndrome among occupants in educational buildings - Syazwan Aizat Ismail; Haslinda Mohamed Kamar; Nazri Kamsah; Mohd Ibtisham Ardani; Nazri Che Dom; Farah Ayuni Shafie; Izwyn Zulkapri; Lim Kuang Hock (International Journal of Public Health Science (IJPHS), 2022)
In educational facilities, good and healthy indoor air quality is critical to ensure students’ focus and academic activities can be carried out efficiently. The goal of this study was to evaluate the link between indoor air quality level with sick building syndrome and health complaints among occupants. A cross-sectional study was conducted which involved 513 occupants. A modified MM040Na questionnaire was used in this study. Occupants’ workspaces were monitored for indoor air quality. The score obtained from the questionnaire and environmental factors were tested using statistical analyses incorporating test of differences namely Chi–Square, t-test, and non-parametric analysis. Logistic regression was conducted to evaluate relationship between exposure and occupants’ complaint. Results shows that some indoor air pollutants (carbon dioxide, formaldehyde, and particulate matter) are related to overall sick building syndrome (Odd Ratio, OR=1.348, 2.493, 1.958 respectively). General score of sick building syndrome (SBS) shows significant relationship with air motion (OR=2.220) and air flow (OR=2.515). Mucosal score of SBS suggest exposure risk towards indoor factors namely formaldehyde (OR=2.799), while dermal effect was associated from the exposure of Particulate (OR=2.88), carbon dioxide (OR=4.000), and air flow (OR=2.679). In educational environments, indoor contaminants have an impact on reported symptoms.